2013
DOI: 10.1007/s12013-013-9626-4
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Based Imaging Probes of the Proteasome

Abstract: Over the years, the proteasome has been extensively investigated due to its crucial roles in many important signaling pathways and its implications in diseases. Two proteasome inhibitors—bortezomib and carfilzomib—have received FDA approval for the treatment of multiple myeloma, thereby validating the proteasome as a chemotherapeutic target. As a result, further research efforts have been focused on dissecting the complex biology of the proteasome to gain the insight required for developing next-generation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…To test the functional status of the proteasome, we employed the activity-based probe Me 4 BodipyFL-Ahx 3 Leu 3 VS. This fluorescent probe binds the active site of catalytic proteasome subunits, allowing detection of changes in constitutive proteasome subunits as well as induction of the immunoproteasome (38,39). We initially confirmed that signal in this assay is inhibited by MG132, a small molecule that similarly binds catalytic sites to inhibit proteasome activity and thereby competes for binding by the activity-based probe (Supplemental Figure 6).…”
Section: Resultsmentioning
confidence: 66%
“…To test the functional status of the proteasome, we employed the activity-based probe Me 4 BodipyFL-Ahx 3 Leu 3 VS. This fluorescent probe binds the active site of catalytic proteasome subunits, allowing detection of changes in constitutive proteasome subunits as well as induction of the immunoproteasome (38,39). We initially confirmed that signal in this assay is inhibited by MG132, a small molecule that similarly binds catalytic sites to inhibit proteasome activity and thereby competes for binding by the activity-based probe (Supplemental Figure 6).…”
Section: Resultsmentioning
confidence: 66%
“…Probably one of the most promising avenues for developing cell-and tissue-permeable selective ubiquitin ABPs for DUBs will rely on the modifi cation of selective small molecule inhibitors of DUBs . Similar approaches have already achieved some preliminary success for other enzymes of the UPS such as E1 enzymes [ 95 ] and proteasome probes [ 96 ]. The limiting step in developing such probes for DUBs is currently a lack of potent, specifi c and selective DUB inhibitors available, however, the community is successfully designing novel generations of selective DUB inhibitors.…”
Section: What Is Next For Chemical Probes Targeting Dubs ?mentioning
confidence: 99%
“…Therefore, many of the best examples of ABPs have been designed to target hydrolases, such as fluorophosphonate probes (1) for serine hydrolases [10] and epoxide and AOMK probes for cysteine proteases (2, 3), [11] which have a reactive nucleophilic residue in the active site and possess a distinct catalytic mechanism. [12] Other such directed ABPs includes probes targeting cathepsins, legumains, [13] caspases, [14] protein arginine methyltransferases (4), [15] proteasomal proteases (5), [16] kinases (6), [17] tyrosine phosphatase, [18] serine/threonine phosphatase, [19] and glycosidases. [20] It may be expected that the design of ABPs for enzyme classes with known covalent inhibitors is, at least in concept, straightforward.…”
Section: Activity-and Affinity-based Probes For Proteomic Profilingmentioning
confidence: 99%